2018
DOI: 10.3390/su10093182
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Water Conservation in Burkina Faso, West Africa

Abstract: Inadequate land management and agricultural activities have largely resulted in land degradation in Burkina Faso. The nationwide governmental and institutional driven implementation and adoption of soil and water conservation measures (SWCM) since the early 1960s, however, is expected to successively slow down the degradation process and to increase the agricultural output. Even though relevant measures have been taken, only a few studies have been conducted to quantify their effect, for instance, on soil eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 74 publications
(110 reference statements)
2
43
0
1
Order By: Relevance
“…1c extends to the Black Volta basin and corroborates the findings of Le, et al 38 who found large-scale land degradation and concluded that around 65% of the entire Volta river basin had undergone human-induced degradation of vegetation productivity. In another study of the Black Volta basin, Nyamekye, et al 39 found that approximately 18% of the natural vegetation in the area was converted into agriculture and non-vegetated surfaces from 1999 to 2011, and this activity was the primary driver of the negative trends they observed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1c extends to the Black Volta basin and corroborates the findings of Le, et al 38 who found large-scale land degradation and concluded that around 65% of the entire Volta river basin had undergone human-induced degradation of vegetation productivity. In another study of the Black Volta basin, Nyamekye, et al 39 found that approximately 18% of the natural vegetation in the area was converted into agriculture and non-vegetated surfaces from 1999 to 2011, and this activity was the primary driver of the negative trends they observed.…”
Section: Discussionmentioning
confidence: 97%
“…Similar patterns were also found by Mueller, et al 46 who characterized the southern coast of West Africa as an "ecoregional extreme" for NDVI increase driven primarily by land management. Similarly, the positive residual trends in parts of Burkina Faso are also the product of both increases in rainfall and land rehabilitation efforts such as stone bunds, agroforestry and mulching 28,39 . The greening trends were also attributed to the expansion of irrigation by Boschetti, et al 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Land-use practices that are favourable or unfavourable to the regeneration of woody species were identified and described by direct observation and semi-directional interviews with populations in the field. The practices with high potential for woody plant regeneration cover soils and water conservation/soils protection and restoration (SWC/SPR) and agroforestry practices, developed in the Sahel region [8,13,[28][29][30]. Land-use practices that may affect the establishment and development of woody plant include: agricultural expansion, bush fire, pasture, urban development, gold panning, and wood harvesting.…”
Section: Land-use Practicesmentioning
confidence: 99%
“…Burkina Faso is a landlocked country with an economy largely based on agriculture. Crop production is largely based on rainfall farming systems and remains vulnerable to climate hazards (1,2). It is in this context that over 13 million (3) people owe their food to a subsistence agriculture strongly dominated by cereals, leguminous, tubers and some minor crops (4).…”
Section: Introductionmentioning
confidence: 99%